Arterial Accidents of the Upper Extremity - Burjel, Jorge; Lanfranconi, Armando; Lanterna, Washington (Cirugía del Uruguay, 1980)
Twelve cases of arterial accidents of the upper extremity (7 traumatics and 5 spontaneous) is analized. At the diagnostic stage the importance of the clinic examination and the indications of the arteriographic study are emphasized.